Complex response of the organism to trauma - Ječmínková, Renáta; Ječmínek, Vladimír; Divák, Jan; Káňová, Marcela; Jor, Ondřej; Tomášek, Kamil; Pleva, Leopold; Holeš, David (Úrazová chirurgie, 2018)
INTRODUCTION: Severe trauma leads to a disruption of the external and internal barrier systems of the affected organism followed by a complex and highly organized reaction triggered by the release of signal molecules from the damaged tissues. These initiate both the activation of the innate immune system and the stimulation of acquired immunity and affect the nervous and hormonal systems. The effort of the organism is to maintain balance and adequacy of this complex reaction and to prevent excessive escalation of originally protective physiological processes. OBJECTIVE: The aim of this work is to provide a comprehensive view of the complex issue of subsequent changes in the body after a severe trauma METHODOLOGY: Review article. CONCLUSION: More and more detailed knowledge and methods of detecting the pathophysiological processes of the body in connection with severe trauma may be the key to other possible therapeutic interventions for these injured patients.
Keywords: imunitní systém - jevy; Immune System Phenomena; Neurosecretory Systems; Shock; neurosekreční systémy; rány a poranění; šok; lidé; Wounds and Injuries; Humans